Movement Disorders Rehabilitation - Chien, Hsin Fen; Barsottini, Orlando Graziani Povoas (Springer International Publishing : Imprint: Springer, 2017)
The aim of this book is to provide a comprehensive overview of the most important movement disorders and describe the rehabilitation tools available for each disease. The management of movement disorders is challenging since most of these diseases are not curable and hardly treatable. Many of the disorders are chronic or degenerative diseases, therefore patients develop motor complications that could improve with rehabilitation interventions. Movement Disorders Rehabilitation intends to serve as a practical guide on the field, attracting the interest of professionals and researchers on the fields of neurology, physical therapy, occupational therapy, speech therapy and other correlated therapies.
Keywords: Medicine.; Neurology.; Rehabilitation medicine.; Occupational therapy.; Physiotherapy.; Speech pathology.; elektronické knihy; electronic books